2022
DOI: 10.1002/jmv.27710
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the hospitalized patients with COVID‐19 receiving atorvastatin: A randomized clinical trial

Abstract: As statins decrease the progression of sepsis and its related mortality, this study aimed to evaluate the effect of atorvastatin on survival and symptom improvement in hospitalized patients with COVID‐19. This randomized controlled trial was performed on 156 hospitalized patients with COVID‐19 in Bojnourd city in 2021. Patients were randomly divided into comparison (standard therapy: hydroxychloroquine + Kaletra®) and intervention groups (atorvastatin 20 mg, SD, plus standard therapy). The main outcomes were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…9 On the other side, another randomized controlled trial suggested that 20 mg atorvastatin per day increased the length of hospital stay (4 days vs. 6, P = 0.001) and the risk of ICU admission (18.4% vs. 1.3%). 21 A high dose of atorvastatin (40 mg) appears to be safe in severe COVID-19 cases. The placebo group had four patients drop out, whereas the Atorvastatin group had one patient experience a signi cant increase in liver enzymes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…9 On the other side, another randomized controlled trial suggested that 20 mg atorvastatin per day increased the length of hospital stay (4 days vs. 6, P = 0.001) and the risk of ICU admission (18.4% vs. 1.3%). 21 A high dose of atorvastatin (40 mg) appears to be safe in severe COVID-19 cases. The placebo group had four patients drop out, whereas the Atorvastatin group had one patient experience a signi cant increase in liver enzymes.…”
Section: Discussionmentioning
confidence: 98%
“…On June 2nd, 2021, we received IRB approval (No. R. 21.04.1300) at Mansoura University, Faculty of Medicine.…”
Section: Consent For Publicationmentioning
confidence: 99%
“…Search strategy yielded 496 potentially relevant records and six fulltext articles were assessed for eligibility. Five RCTs [2][3][4][5][6] were selected for the meta-analysis (Supplementary file) and a total of 1132 patients were included, 556 in the intervention group and 576 in the control group (placebo or standard protocol). Of the included trials, four used atorvastatin (20 mg/day [2,3] or 40 mg/day [4,5]) and one used rosuvastatin (40 mg/day) [6] as treatment for hospitalized patients with COVID-19 (Supplementary file).…”
Section: Effects Of Statins On Clinical Outcomes In Hospitalized Pati...mentioning
confidence: 99%
“…Five RCTs [2][3][4][5][6] were selected for the meta-analysis (Supplementary file) and a total of 1132 patients were included, 556 in the intervention group and 576 in the control group (placebo or standard protocol). Of the included trials, four used atorvastatin (20 mg/day [2,3] or 40 mg/day [4,5]) and one used rosuvastatin (40 mg/day) [6] as treatment for hospitalized patients with COVID-19 (Supplementary file). Overall, the RCTs had a low risk of selection and attrition bias, but 40% presented a potential risk for performance, detection, and reporting bias.…”
Section: Effects Of Statins On Clinical Outcomes In Hospitalized Pati...mentioning
confidence: 99%
“…Inconsistent with these results, an RCT showed deleterious effects of statins in hospitalized COVID-19 patients. Atorvastatin in addition to standard care delayed symptom improvement and subsequently increased hospitalization length (1.71-fold delayed remission; HR, 1.70; 95% CI, 1.22–2.38; p = 0.002) [ 46 ].…”
Section: Clinical Studies Investigating the Benefits Of Statins In Co...mentioning
confidence: 99%